Direct utilization of unpurified natural pyrite for sustainable peroxydisulfate activation: Harnessing surface organic impurities as chemical “ignition switches” - Rui Zhou; Lilu Ding; Zhenghong Wu; Shuai Liu; Zhonghui Han (Journal of Hazardous Materials, 2026)

A novel thermo-hydro-mechanical coupled model for soil-rock mixtures incorporating preferential flow: A case study of Hesigewula mine dump - Jian Cao; Zihan Zhou; Lingfei Zhang; Zhonghui Chen; Zhongxin Wang; Xiangyu Zeng; Pei Han (Engineering Geology, 2026)

High-entropy prussian blue analogue for rapid and efficient adsorptive removal of thallium from water: Performance and mechanism insights - Ying He; Changhao Cai; Yingming Ma; Azhar Mahmood; Zhenbang Liu; Wei Wang; Yu Bao; Zhonghui Sun; Li Niu; Carlos Ruiz Canovas; Dongxue Han; Tangfu Xiao (Journal of Environmental Chemical Engineering, 2026)

Hollow MOFs-based biomimetic encoded microspheres as versatile probes for dual-mode ratiometric fluorescence sensing platform coupling instrumental and smartphone-assisted analysis of Sudan I - Xueyong Qiao; Rongrong Yang; Zhonghui Han; Lei Lü; Xiaolei Zhao; Jinxing He (Analytica Chimica Acta, 2026)

In-situ remediation of Cr(VI) contaminated groundwater by synergistic oxalic acid-ethanol reduction: Mechanistic insights and sand tank validation - Wenwen Lin; Yang Liu; Zhonghui Han; Chengye Wang; Xiaoxu Zhang; Taigang Ma; Hejun Ren (Journal of Cleaner Production, 2025)

Unraveling structure-2e− ORR selectivity correlations in oxygen-doped carbon catalysts: Defects and carboxyl groups as dual active sites for enhanced H2O2 electrosynthesis and wastewater decontamination - Fangyuan Liu; Zhonghui Han; Lijuan Li; Xianchuan Li; Chunpeng Zhang; Hejun Ren (Chemical Engineering Journal, 2025)

Reduction in Serum Concentrations of Uremic Toxins Driven by Bifidobacterium Longum Subsp. Longum BL21 is Associated with Gut Microbiota Changes in a Rat Model of Chronic Kidney Disease - Yao Dong; Zhonghui Gai; Mei Han; Jiaqi Xu; Kang Zou (Probiotics and Antimicrobial Proteins, 2025)
Gut microbiota dysbiosis and consequent impairment of gut barrier function, culminating in elevated levels of uremic toxins, are prevalent in chronic kidney disease (CKD) patients. These toxins, notably indoxyl sulphate (IS), indole-3-acetic acid (IAA), and trimethylamine oxide (TMAO), are implicated in a spectrum of CKD-related complications, including cardiovascular disease, bone and mineral disorders, and inflammation. The specific impacts of various probiotics on these CKD manifestations remain unexplored. This study delved into the potential of dietary probiotic interventions, particularly Bifidobacterium longum subsp. longum BL21, to modulate gut microbiota and mitigate metabolic disorders in a CKD rat model. Over a six-week period, we administered a dietary regimen of BL21 and conducted comprehensive analyses, including serum uremic toxin quantification and 16S rRNA gene sequencing, to systematically profile gut microbial alterations at the phylogenetic level. Our findings reveal that BL21 intervention significantly ameliorated CKD-induced disruptions in gut microbial populations, enhancing both microbial richness and the relative abundance of key taxa. Importantly, BL21 appeared to exert its beneficial effects by modulating the abundance of crucial species such as Barnesiella and Helicobacter . Functionally, the intervention markedly normalized serum levels of IS, IAA, and TMAO, while potentially attenuating p-cresol sulphate (PCS) and p-cresol glucuronide (PCG) concentrations. Consequently, BL21 demonstrated efficacy in regulating gut microbiota and curtailing the accumulation of uremic toxins. Our results advocate for the utilization of BL21 as a dietary intervention to diminish serum uremic toxins and re-establish gut microbiota equilibrium at the phylogenetic level, underscoring the promise of probiotic strategies in the management of CKD.

SIZ1-mediated SUMOylation of CPSF100 promotes plant thermomorphogenesis by controlling alternative polyadenylation - Zhibo Yu; Jun Wang; Cheng Zhang; Qiuna Zhan; Leqian Shi; Bing Song; Danlu Han; Jieming Jiang; Junwen Huang; Xiaolin Ou; Zhonghui Zhang; Jianbin Lai; et al. (Molecular Plant, 2024)

In vitro and in vivo genome-based safety evaluation of Lacticaseibacillus rhamnosus LRa05 - Ting Chen; Yawen Shao; Yinan Zhang; Yunjiao Zhao; Mei Han; Zhonghui Gai (Food and Chemical Toxicology, 2024)

Biodegradation of atrazine with biochar-mediated functional bacterial biofilm: Construction, characterization and mechanisms - Bo Zhang; Jingdan Zhang; Yuping Wang; Jianhua Qu; Zhao Jiang; Xu Zhang; Yue Tao; Yifan Wang; Zhonghui Kang; Songting Han; Jingyi Zhang; Ying Zhang (Journal of Hazardous Materials, 2024)

Preparation of slow-release fertilizers by electrolytic manganese residue and alkali-activated laterite-based geopolymers: Mn release effects on Guizhou white tea seedlings growth - Linpei Han; Yunlin Yu; Zhonghui Xu; Jiancheng Shu; Shaojian Zhang; Liping Ning; Shimin Gao; Jie Xu; Chao Li (Journal of Cleaner Production, 2024)

Strong enhancement on electron transfer pathway of peroxymonosulfate activation for rapid organic pollutant degradation in wastewater by iron encapsulated into nitrogen-doped carbon: Iron-cores as electron supply stations - Taigang Ma; Hejun Ren; Meijun Liu; Jinhao Duan; Zhonghui Han; Rui Zhou (Chemical Engineering Journal, 2024)

Encoding CsPbX3 perovskite quantum dots with different colors in molecularly imprinted polymers as fluorescent probes for the quantitative detection of Sudan I in food matrices - Jinxing He; Lu Yu; Yandu Jiang; Lei Lü; Zhonghui Han; Xiaolei Zhao; Zhixiang Xu (Food Chemistry, 2023)

Mn release behaviors from electrolytic manganese residue-based slow-release fertilizer using acid/alkali-activated geopolymers as binders: A comparative study - Linpei Han; Zhonghui Xu; Jiancheng Shu; Yunlin Yu; Liping Ning; Shimin Gao; Jie Xu; Chao Li (Journal of Cleaner Production, 2023)

Spatial asynchrony matters more than alpha stability in stabilizing ecosystem productivity in a large temperate forest region - Xuetao Qiao; Yan Geng; Chunyu Zhang; Zhuoxiu Han; Zhonghui Zhang; Xiuhai Zhao; Klaus von Gadow (Global Ecology and Biogeography, 2022)
Aim Understanding the biodiversity–stability relationship has become a central issue in ecology and conservation biology. Although the stabilizing effects of tree species diversity on ecosystem productivity are well recorded in small local communities, they remain poorly understood across scales (from local to larger spatial scales). This study evaluates biodiversity–stability effects from local to larger spatial scales in a large temperate forest region, considering a range of environmental conditions and environmental heterogeneity. Location North‐eastern China ( c . 700,000 km 2 ). Time period 2005–2017. Major taxa studied Woody plants. Methods We define stability as the temporal invariability of biomass productivity. Regional metacommunities representing larger spatial scales were developed by aggregating multiple sets of local field plots. Simple regression analysis was used to test biodiversity–stability relationships in metacommunities. Piecewise structural equation modelling was then used to disentangle the effects of diversity and abiotic variables on forest stability at local and larger spatial scales. Multiple mixed‐effects regression models were used to determine the relative contribution of individual predictive variables to stability across spatial scales. Results We found that local diversity (alpha diversity) was positively related to the stability of local communities (alpha stability), whereas species turnover across space (beta diversity) was positively related to asynchronous dynamics among local communities (spatial asynchrony), regardless of whether abiotic factors were considered or not. We also found that environmental conditions and environmental heterogeneity affected forest stability across scales. The effect of spatial asynchrony on gamma stability was greater than that of alpha stability. Main conclusions Our results imply that spatial asynchrony is a key to maintaining the stability of ecosystem productivity within a large temperate forest region. We suggest that diverse forests and heterogeneous landscapes should be sustained at multiple spatial scales to buffer the negative effects of climate change and forest degradation.

Estimating cloud base height from Himawari-8 based on a random forest algorithm - Zhonghui Tan; Juan Huo; Shuo Ma; Ding Han; Xin Wang; Shensen Hu; Wei Yan (International Journal of Remote Sensing, 2021)

Preparation of non-sintered lightweight aggregates through co-mechanochemical treatment of oil-contaminated drill cuttings, circulation fluidized bed combustion fly ash, and quicklime - Xiaoyue Chen; Zhonghui Xu; Zhengzhen Yao; Qin Shuai; Zao Jiang; Xi Peng; Yu Li; Ran An; Xin Jiang; Han Li (Environmental Science and Pollution Research, 2020)